Neuroimaging studies of striatum in cognition part II: Parkinson's disease - Hanganu, Alexandru; Provost, Jean-Sebastien; Monchi, Oury (Frontiers in Systems Neuroscience, 2015)
In recent years a gradual shift in the definition of Parkinson’s disease (PD) has been established, from a classical akinetic-rigid movement disorder to a multi-system neurodegenerative disease. While the pathophysiology of PD is complex and goes much beyond the nigro-striatal degeneration, the striatum has been shown to be responsible for many cognitive functions. Patients with PD develop impairments in multiple cognitive domains and the PD model is probably the most extensively studied regarding striatum dysfunction and its influence on cognition. Up to 40% of PD patients present cognitive impairment even in the early stages of disease development. Thus understanding the key patterns of striatum and connecting regions’ influence on cognition will help develop more specific approaches to alleviate cognitive impairment and slow down its decline. This review focuses on the contribution of neuroimaging studies in understanding how striatum impairment affects cognition in PD.